Systematic analysis and optimization of grain postproduction operation patterns in south China - YING Xia-fang; ZHENG Wen-zhong; HE Yong (浙江大学学报. 农业与生命科学版, 2005)
Based on the analysis of present situation and characteristics of grain postproduction system consisting of three indexes, i.e. treatment cost, treatment time consumption and grain quantity loss in Zhejiang Province, P. R. China, a dynamic program model was put forward to analyze both loss and efficiency of process of grain post-harvest systems. The results of discussion show that it is an effective measure to improve the function of grain postproduction system in both efficiency and losses by applying precision farming technology and equipment.